Investigating the Impact of Globalization on the Development of Islamic Family Law: A Case Analysis of Modernizing Muslim Countries - Luqman Saputra (PT. Anagata Sembagi Education, 2024)
Abstract This research aims to investigate the impact of globalization on the development of Islamic family law in modernizing Muslim countries. Using a qualitative approach and case study analysis, this research explores how globalization affects the legislative process, legal interpretation, court practice, and societal responses to Islamic family law in the context of increasingly complex global dynamics. The results show that globalization has brought significant changes in the paradigm of Islamic family law, with the adoption of more uniform and universal aspects of the law, along with adjustments to global values such as human rights and gender equality. However, this adoption is often at odds with traditional values and local interpretations of Islamic family law. In addition, globalization has also influenced interpretations of Islamic family law, court practices and community responses. There are debates and diverse interpretations of the principles of Islamic family law in the context of modernity and globalization, as well as the influence of globalization on community responses to changes in Islamic family law. The implication of this research is the need for a more flexible and inclusive approach in developing Islamic family law in the era of globalization. Policy recommendations include strengthening dialogue between legal authorities, scholars, and civil society to reach a more inclusive agreement in updating and adapting Islamic family law to diverse global and local values.